Giant Lymphedema Scrotum: A Case Report - Tampubolon, Nelsi Marintan; Wardaya, Setya Anton Tusara; Wibowo, Syaeful Agung (Open Access Health Scientific Journal, 2025)
Background: Scrotal lymphedema is an abnormal accumulation of protein-rich fluid in the soft tissue area of the scrotum/penoscrotal area as well as deformity of the genitals due to abnormal lymphatic drainage. Lymphedema is classified as primary (idiopathic) or secondary according to its etiology. Secondary lymphedema can occur due to infection, one of which is Mycobacterium TB infection. Conservative or surgical methods such as lymphangioplasty, complete excision of tissue, local tissue reconstruction can be performed.Methods: Using the case report method and 1 sample, Mr. S, 42 years old, male gender.Results: In this case is a secondary case related to a history of hydrocele surgery or extrapulmonary TB infection. In scrotal TB can appear as unilateral or bilateral involvement with acute or chronic painful or painless scrotal swelling. This is also evidenced by the results of a biopsy where there is granulomatous inflammation.Conclusion: Scrotal lymphedema is a challenging problem that causes physical and emotional disability. The choice of appropriate management, whether conservative or surgical, is very important for the patient's quality of life.